Influence of Magnesium Sulphate on Cholecystokinin, Hunger, and Obesity - Kreft, Samo; Štrukelj, Borut (Progress in Nutrition, 2021)
Aim: Magnesium has many important functions in the body and one of its less known roles is its contribution to weight management. It triggers the release of cholecystokinin from the small intestines, which leads to suppression of hunger, lowers food intake, and reduces body weight. In this article we reviewed research that investigates this process as well as the individual steps of this pathway. Methods: Comprehensive literature search was done with several databases and research was critically evaluated. Results: The ability of magnesium to stimulate the release of cholecystokinin was demonstrated in many animal and human studies. The influence of cholecystokinin on hunger/satiety sensation and or food intake was shown in several experimental models. Some studies demonstrated the overall link between magnesium intake and obesity. Conclusions: Even if there is still some controversy, most of the studies show that magnesium suppresses hunger, lowers food intake, and reduces body weight. The most probable mechanism is through magnesium stimulating cholecystokinin, which plays an important inhibitory role in the control of feeding behavior.